Studies in South African marine molluscan chemistry - Bromley, Candice Leigh (Rhodes University, Faculty of Science, Department of Chemistry, 2011)
This thesis investigates the variability occurring in the secondary metabolites produced by three South African marine molluscs. Chapter Two discusses the isolation and spectroscopic structure elucidation of the metabolites isolated from two Siphonaria species. The re-investigation of Siphonaria capensis yielded siphonarienfuranone (2.2) as the only common polypropionate isolated from both the 1998 and 2009 collections of S. capensis from the same areas suggesting possible seasonal or genetic variation in polypropionate production. The sterol cholest-7-en-3,5,7- triol (2.33) was also isolated form the 2009 collection of S. capensis and this is the first time this compound has been isolated from a Siphonaria species. The second species, Siphonaria oculus is closely related to S. capensis and the investigation into the former's secondary metaboliteproduction revealed 2.2 as a major metabolite suggesting an inter-species overlap in polypropionate production. Three new polypropionate metabolites, 2.35, 2.36 and 2.37 were also isolated from S. oculus. An unsuccessful attempt was made to establish the absolute configuration of 2.37 using the modified Mosher's method and the limited amount of 2.37 available prevented any further attempts at resolving the absolute configuration of this compound. The 1H NMR analysis of the defensive mucus collected directly from S. oculus revealed the presence of the acyclic polypropionate 2.37 as a minor metabolite. The absence of characteristic signals for the furanone containing compounds 2.2, 2.35 and 2.36, might suggest that these compounds cyclise from a hypothetical acyclic precursor (2.38) during standard work up of bulk acetone extracts of Siphonaria species. Chapter Three discusses the re-isolation and spectroscopic structure elucidation of the metabolites isolated from the nudibranch, Leminda millecra. Three known natural products, millecrone A (3.1), 8-hydroxycalamenene (3.6) and cubebenone (3.8) were re-isolated from our 2010 collection of L. millecra, as well as the new minor metabolite 8-acetoxycalamenene (3.16). The cytotoxic prenylated toluquinones and toluhydroquinones (3.9-3.15) initially isolated from the 1998 collection of L. millecra were not found in the 2010 collection supporting the hypothesis that these compounds may be of fungal origin. L. millecra clearly shows variability in the compounds sequestered by this species with millecrone A (3.1) being the only common metabolite in the three investigations of L. millecra to date. An unsuccessful attempt was made to establish the absolute configuration of 3.1, 3.6 and 3.8 through initial LAH reduction of the ketone moiety contained in 3.1 and 3.8 and esterification of the resultant diastereomeric alcohol mixtures and the phenol functionality in 3.6 with (1S)-camphanic chloride. Crystallisation of the (S)- camphanate esters of 3.6 and 3.8 for X-ray analysis were unsuccessful, while the unexpected conjugate addition of a hydride in 3.1 resulted in complex diastereomeric mixtures which could not be separated by HPLC.
Keywords: Mollusks -- South Africa; Marine invertebrates -- South Africa; Marine metabolites -- South Africa; Chemical oceanography -- South Africa